2015
DOI: 10.1155/2015/969450
|View full text |Cite
|
Sign up to set email alerts
|

Fishery Landing Forecasting Using Wavelet-Based Autoregressive Integrated Moving Average Models

Abstract: The accuracy of the wavelet-ARIMA (WA) model in monthly fishery landing forecasting is investigated in the study. In the first part of the study, the discrete wallet transform (DWT) is used to decompose fishery landing time series data. Then ARIMA, as a powerful forecasting tool, is implemented to predict each wavelet transform subseries components independently. Finally, the prediction results of the modeled subseries components are summed to formulate an ensemble forecast for the original fishery landing ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…[8], in his study of hybrid wavelet and adaptive neuro-fuzzy inference system for drought forecasting stated that wavelet analysis is one of the most powerful tools to study time series. In another study, [9], described wavelet analysis as a multi-decomposition analysis that provide information for time and frequency domains and provide useful decompositions of the original time series for the wavelet-transformed data to improve the power of a forecasting model. Wavelet is a tool in time series forecasting whose importance is applied by many researchers.…”
Section: Discrete Wavelet Transform (Dwt)mentioning
confidence: 99%
“…[8], in his study of hybrid wavelet and adaptive neuro-fuzzy inference system for drought forecasting stated that wavelet analysis is one of the most powerful tools to study time series. In another study, [9], described wavelet analysis as a multi-decomposition analysis that provide information for time and frequency domains and provide useful decompositions of the original time series for the wavelet-transformed data to improve the power of a forecasting model. Wavelet is a tool in time series forecasting whose importance is applied by many researchers.…”
Section: Discrete Wavelet Transform (Dwt)mentioning
confidence: 99%
“…For example, the models only depict the current picture of the fishery using the time series trend and lack the power of prediction. Other models such as bootstrap, state-space [13], and Bayesian [12,13,14,15] have also been applied with little success. The time-series approach, however, has been indispensable in understanding natural resources systems and the development of better management policies [16].…”
Section: Introductionmentioning
confidence: 99%
“…These studies made a brief analysis of the correlation between variables, self-correlation, and cross-correlation using non-linear functions to find functional relationships to introduce different models [2]. On the other hand, the wok in [10] predicted the environmental variability in the anchovy fishery in the northern zone of Chile, through the development of spatio-temporal indicators of the ecosystem, statistical relationships between indicators, GIS functions (Geographical Information Systems), and ANN models, offering an integration in the prediction of anchovy abundance.With respect to other statistical techniques implemented to forecast fishing landings, there was the application of a hybrid model studied by [11], in which the potentialities of autoregressive models integrated moving averages (ARIMA) were combined with wavelet theory to enhance the precision of fishing landings' forecasts in Malaysia. Their study found that the combined model provided more accurate forecasts of fishing landing series than the individual ARIMA model.…”
mentioning
confidence: 99%
“…With respect to other statistical techniques implemented to forecast fishing landings, there was the application of a hybrid model studied by [11], in which the potentialities of autoregressive models integrated moving averages (ARIMA) were combined with wavelet theory to enhance the precision of fishing landings' forecasts in Malaysia. Their study found that the combined model provided more accurate forecasts of fishing landing series than the individual ARIMA model.…”
mentioning
confidence: 99%